Research progress on the application of bedside lung ultrasound in ICU nursing (床旁肺部超声在ICU护理中应用的研究进展) - TAN Huiting (谭慧婷); WANG Fengying (王凤英); LI Fangfang (李芳芳); GUO Yanyun (郭艳云); XUE Chao (薛超) (中西医结合护理)
With the development of critical care medicine, bedside lung ultrasound, as an effective auxiliary diagnostic tool, has been widely used in intensive care unit nursing. This study reviewed the application progress of bedside lung ultrasound in ICU nursing, including the path of ICU nurses using bedside lung ultrasound to guide intensive care work, the specific application of bedside lung ultrasound in ICU nursing work, the obstructive factors in ICU nurses using bedside lung ultrasound to guide intensive care practice and effective ways to improve. The aim is to provide reference for ICU nursing practice and promote the standardized application of bedside lung ultrasound technology, so as to improve the nursing effect of severe patients. (床旁肺部超声作为一种有效的辅助诊断工具, 在重症监护病房护理工作中应用广泛。本研究综述了床旁肺部超声在ICU护理中的应用进展, 主要包括ICU护士运用床旁肺部超声指导重症护理工作的路径、床旁肺部超声在ICU护理工作中的具体应用、ICU护士运用床旁肺部超声指导重症护理实践中的阻碍因素以及有效的提高途径, 旨在为ICU护理实践提供参考, 促进床旁肺部超声技术的规范化应用, 从而提高重症患者的护理效果。)